Power Industry Economics, Renewable Energy Systems, Electric Vehicles Engineering Design & Applications - Sankhwar, Pravin (Power Industry Economics, Renewable Energy Systems, Electric Vehicles Engineering Design & Applications, 2025)
The power industry is enriched by the presence of diverse generations, from fossil fuels to renewable energy. Energy crises from the depletion of fossil fuels have been an area of concern during the planning of a sustainable future. Energy economics, by meeting the supply and demand changes, opportunity costs, and shifting industry from fossil fuels to renewable energy, becomes the basis of research. Fully electric vehicles (EVs) comprise an electric motor driven by a set of battery packs. Their adoption is increasing the extent of decarbonization of the transportation and energy sector. Studies have documented that EVs reduce emissions by a significant proportion when compared to conventional internal combustion engine (ICE) automobiles. Limitations from charging infrastructure and prospects of higher operating voltage and power capacities to modeling a battery circuit using a transfer function model became a decision maker in integration with renewable energy power generation resources from solar and wind. Wind and solar energy are available per India’s wind speed and the solar map is the solution for increasing the renewable energy penetration into the power industry. Hydrogen production and storage to run fuel cell-based vehicles are feasible solutions per the MATLAB model and characteristics curves for the hydrogen output from the electrolyzer. Both fully electric vehicles and hydrogen-based fuel cell electric vehicles will decarbonize the market with reduced carbon emissions. The use of an integrated system of solar photovoltaics for generating hydrogen from an electrolyzer enhances the overall process and efficiency without depending on fossil fuels. The power industry benefits from engineering design in compliance with safety standards when implementing high-energy output charging stations. Additionally, major industry practices for the safe adoption of solar photovoltaics, wind turbines, electric vehicles, electric vehicle charging stations, hydrogen generation, hydrogen storage, and fuel cell-based electric vehicles become a motivator for this research work. For example, some jurisdictions across the globe have varying standards for the safety operability of electrical equipment where it is ensured that the users are exposed to limited electrical hazards without compromising the improved experience from shifting technology in the power and transportation industry.